A history of Ghana. - Ward, W. E. F. (William Ernest Frank), 1900-1994. (London, Allen & Unwin, 1958)
From earliest times through its establishment as an independent state.
Originally published in 1948 under title: A history of the Gold Coast.
Includes bibliographical references (pages 13-14).
Also issued online.
Keywords: Ghana -- History; History